2017
DOI: 10.1017/aae.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Trading Based on Knowing the Wasde Report in Advance

Abstract: Abstract. Past research shows that prices move in response to World Agricultural Supply and Demand Estimates (WASDE) reports immediately prior to and after a report. This research develops trading models based on knowing the next WASDE report in advance. This should help traders evaluate investments to predict information contained within the report and in determining how best to use such forecasts. The price-forecasting models use regressions against the ratios of ending stocks to use. Results show a steady i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with previous research that has identified the importance of WASDE reports using different procedures in a variety of markets (Adjemian, 2012;Milacek and Brorsen, 2017). These studies have essentially inferred USDA reports have value from volatility responses, which relies on the assumption of market efficiency in adjusting to new information in short intervals.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with previous research that has identified the importance of WASDE reports using different procedures in a variety of markets (Adjemian, 2012;Milacek and Brorsen, 2017). These studies have essentially inferred USDA reports have value from volatility responses, which relies on the assumption of market efficiency in adjusting to new information in short intervals.…”
Section: Discussionsupporting
confidence: 92%
“…McKenzie (2008) used a Hamilton‐type (1992) approach to demonstrate that “there were periods when having advanced knowledge of the August report would have significantly adjusted rational agent expectations, augmenting information already embodied in futures prices” (p. 365). Milacek and Brorsen (2017) developed trading models based on knowing the WASDE report in advance to estimate potential trading returns from using WASDE report predictions in the days before the report. Their findings reveal that the perfect foresight trading signal generated an average daily return of 1.11 cents per bushel for corn with July, September, and October reports generating the highest returns.…”
Section: Indirect Measures Based On Informational Value Trading Retur...mentioning
confidence: 99%